Mental toughness of martial art athletes based on age and gender (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Mental toughness is one of psyichological factors when athlete doing training or match. The function of mental toughness is to keep the atlethes fit when they have some difficulties in a match, feel the pressure during the match, and take behavior control so that they will not get stressed easily. This research aims to know mental toughness condition of the athletes through the age and gender. Data analysis techniques that we used for this research are descriptive statistic and cross tab. The sample was taken from 174 martial art atheletes (Age = 19.69 Â± 2.89 ). Instrument of mental toughness refers to mental toughness dimension made by Clogh et al. (2001) which is; control, commintment, challenge, and confidence. The result of this research shows that most of them are on the high level of mental thoughness, and the majority is the men at the age of 19 to 22. In addition, the relationship that we observed in this study emphasized the need of coping and optimism training in mental toughness intervension.